2004
DOI: 10.1016/s0377-1237(04)80106-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of Solitary Seizures

Abstract: Background :Solitary seizure is one of the controversies in neurology. This study was taken up to study the clinical profile of solitary seizure and the factors related to seizure recurrence with a view to evolve guidelines for management. Methods : We studied 150 cases of solitary seizure. All our patients were males. The age varied from 18-52 years. The diagnosis of seizure was confirmed with history. Apart from clinical neurological examination, blood counts, urinalysis and screening investigations to exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…[ 15 ] In patients with first-onset seizure, Hakami et al, showed EEG abnormality in 31% with slowing in 57% and epileptiform discharges in 42%. [ 11 ] Jha[ 24 ] studied 150 cases of solitary seizures. EEG was done in all patients, and was abnormal in 22% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] In patients with first-onset seizure, Hakami et al, showed EEG abnormality in 31% with slowing in 57% and epileptiform discharges in 42%. [ 11 ] Jha[ 24 ] studied 150 cases of solitary seizures. EEG was done in all patients, and was abnormal in 22% of patients.…”
Section: Discussionmentioning
confidence: 99%